TEMPERATURE MEASUREMENTS IN THE CRATER OF MOUNT EREBUS, ROSS ISLAND, ANTARCTICA - ミウラ, サトシ; カミヌマ, カツタダ /; MIURA, Satoshi; KAMINUMA, Katsutada; DIBBLE, Raymond R. (National Institute of Polar Research, 1988)
P(論文) Surface temperature distribution in the crater of Mount Erebus, Ross Island, Antarctica, was surveyed during the 1986-1987 field season using an infrared radiation thermometer. A convecting lava lake with the diameter of about 20 to 30m was observed in the Main Crater. The surface temperature of the lava was indicated to be about 800℃ and the ground temperature by an active vent from which eruptions with ash ejection sometimes occurred was about 80℃. Except for some portions not covered by snow or ice, the ground temperature on the crater wall was below 0℃. departmental bulletin paper